Recent Advances in Engineering of Media for Enzymatic Catalysis with Lipase: A Review - Li, Yuanyuan; Wang, Fen; Shen, Yingqiang; Wang, Anming; Chen, Canyu (Asian Journal of Chemistry, 2014)
Most lipases display good solubility and catalytic activity in non-aqueous media. In many types of non-aqueous media, such as ionic liquids, supercritical fluids, fluorous solvents etc., substrates and products are soluble and are therefore able to diffuse during reactions, which might often be beneficial to the lipase activity. Lipases often exhibit higher activity and stability in non-aqueous media than in aqueous environments. In addition, after reactions are carried out in novel media, a simple separation procedure might be included with the reaction process to facilitate improved purification of the products without using chromatographic separation or liquid-liquid extraction. This review focuses on novel medium for lipase catalysis, such as fluorous solvents, ionic liquids, supercritical fluids, etc. Some future perspectives and challenges facing in the media for enzymatic synthesis with lipase are also proposed.